The Message of Merciful Love Towards our Neighbour - Dziuba, Adndrzej (Studia Teologiczne Białystok Drohiczyn Łomża, 2022)
Jesus basically expects each human being to carry out the deeds of mercy, whose source is the love for God. It is a desire for love and mercy. Mercy is another name for love. The scale of man’s answer is the extent of their love. The works of mercy are: deeds, words, prayers, sufferings and striving for perfection, for holiness, perceived as the imitation of Christ and love of one's neighbor. Our eyes, ears, tongue, hands, legs and heart should practice love toward others. Love for God must not be separated from our neighbors’ love. This a call for man to return to God, to live in the spirit of mercy, which means one’s full union with God in the fullness of love and in the freedom of God’s children. Mercy it the best answer given for various questions and pains of today’s world. Practicing mercy is neither beyond human capacities nor beyond the possibilities of human nature.